Prispevki k slovnici slovenskih medmetov - Snoj, Marko (Slavistična revija, 2022)
The article addresses three sets of questions. (1) What are interjections; what subtypes of interjections are there and how should they be presented in the new digital Slovar slovenskega knjižnega jezika (Dictionary of the Slovenian standard language)? (2) What is the nature of interjections and in what segmental and suprasegmental properties distinguish them from the rest of the lexicon? What are their morphological properties? (3) What is the origin of interjections?
Keywords: besedna vrsta; categorical properties; conversion; interjection; kategorialne lastnosti; konverzija; medmet; parts of speech; Slovene; slovenščina